Gas barrier laminate
The gas barrier laminate with a polyurethane resin and silane coupling agent top coat, combined with an anchor coat and inorganic layers, addresses durability and adhesion issues, ensuring robust barrier properties under hot water treatments.
Patent Information
- Application Number
- JP2023113313
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
AI Technical Summary
Conventional gas barrier films suffer from poor durability against bending, peeling of inorganic layers, and loss of gas barrier properties under hot water treatments like boiling and retort, with aluminum films reacting with hot water to lose adhesion and metallic appearance.
A gas barrier laminate configuration comprising a base material, gas barrier layer, and top coat layer, where the top coat is a mixture of polyurethane resin and silane coupling agent, with the polyurethane resin having hydroxyl groups, and optionally including silicon, titanium, tin, zinc, aluminum, or magnesium oxides or nitrides, and an anchor coat layer for improved adhesion.
The laminate maintains excellent oxygen and water vapor barrier properties even after hot water treatments, with improved adhesion and resistance to bending, suitable for food packaging and electronic applications.
Smart Images

Figure 2025010972000004 
Figure 2025010972000005 
Figure 2025010972000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas barrier laminate. More specifically, the present invention relates to a gas barrier laminate that has excellent oxygen barrier properties and water vapor barrier properties, and that maintains excellent oxygen barrier properties even after bending treatment or hot water treatment such as retort treatment. [Background technology]
[0002] Conventionally, packaging materials used for food, medicine, etc. are required to have gas barrier properties to protect substances that are sensitive to oxygen and moisture. In addition, gas barrier materials used for electronic devices and electronic components such as solar cells and organic electroluminescence (EL) devices require even better gas barrier properties. For this reason, films laminated with polymer resin compositions such as polyvinyl alcohol (PVA), ethylene-vinyl alcohol copolymer (EVOH), and polyvinylidene chloride resin (PVDC) have been used as packaging materials.
[0003] However, the gas barrier properties of PVA and EVOH are highly dependent on humidity, and the water vapor barrier properties in particular are easily and significantly reduced under high humidity conditions. In addition, PVDC contains a large amount of chlorine in the film, which causes environmental hazards when it is disposed of.
[0004] In view of this, gas barrier films have been developed in which inorganic substances such as metallic aluminum, silicon oxide, and aluminum oxide are provided on the surface of a plastic film by physical vapor deposition or chemical vapor deposition (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-188658 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the gas barrier film described in Patent Document 1 has poor durability against bending, and the vapor deposition layer is prone to cracking, which leads to a decrease in gas barrier properties. Furthermore, conventional gas barrier films have low interlayer adhesion between the plastic film and the inorganic material vapor deposited on its surface, and are easily peeled off when repeatedly bent, resulting in a loss of gas barrier properties.
[0007] In recent years, there has been an increasing demand for resistance to hot water treatment (hereinafter also referred to as boiling treatment) and pressurized hot water treatment (hereinafter also referred to as retort treatment). However, when boiling treatment or retort treatment is performed on an aluminum-deposited film in which aluminum is deposited on a plastic film, the adhesion of the aluminum thin film decreases and the gas barrier performance decreases. In addition, conventional gas barrier films have problems such as the loss of the metallic appearance of the aluminum thin film due to reaction with hot water, unevenness in the appearance, and reduced light-shielding properties.
[0008] The gas barrier film described in Patent Document 1 also cannot maintain its gas barrier properties and adhesion when subjected to retort treatment, which is more severe than boiling treatment.
[0009] The present invention has been made in view of the above-mentioned conventional inventions, and has an object to provide a gas barrier laminate which has excellent oxygen barrier property and water vapor barrier property, and which has excellent oxygen barrier property even after bending treatment or hot water treatment such as retort treatment. [Means for solving the problem]
[0010] The gas barrier laminate of the present invention, which solves the above problems, mainly comprises the following components.
[0011] (1) A gas barrier laminate comprising a substrate, a gas barrier layer, and a topcoat layer laminated in this order, the topcoat layer being made of a mixture of a polyurethane resin and a silane coupling agent, the polyurethane resin including a polyhydroxyurethane resin having a hydroxyl group.
[0012] With such a configuration, the gas barrier laminate has excellent oxygen barrier properties and water vapor barrier properties, and also has excellent oxygen barrier properties after bending treatment or hot water treatment such as retort treatment.
[0013] (2) The gas barrier laminate according to (1), wherein the top coat is formed by applying an aqueous dispersion of a polyhydroxyurethane resin, and in the aqueous dispersion, at least a portion of the carboxy groups in the polyhydroxyurethane resin structure are neutralized with a basic compound.
[0014] With this configuration, the gas barrier laminate has improved dispersibility in the polyhydroxyurethane aqueous dispersion and improved film-forming properties when formed into a coating film, and is more likely to exhibit gas barrier properties and protective function of the gas barrier layer. Furthermore, the gas barrier laminate is easily dried and cured sufficiently even at low temperatures in a short time, and production costs can be easily reduced.
[0015] (3) The gas barrier laminate according to (1) or (2), wherein the gas barrier layer contains at least one of silicon, titanium, tin, zinc, aluminum, indium, or magnesium, and an oxide or nitride thereof.
[0016] With such a configuration, the gas barrier laminate is likely to form a dense continuous film, and has superior gas barrier properties.
[0017] (4) The gas barrier laminate according to any one of (1) to (3), wherein the gas barrier layer contains at least one of aluminum, silicon oxide, and aluminum oxide.
[0018] With such a configuration, the gas barrier laminate is particularly suitable for use as a food packaging film.
[0019] (5) The gas barrier laminate according to any one of (1) to (4), further comprising an anchor coat layer between the substrate and the gas barrier layer, the anchor coat layer being formed from at least one resin selected from the group consisting of polyester resins, polyurethane resins including polyhydroxyurethane resins having hydroxyl groups, acrylic resins, polycarbodiimide resins, oxazoline group-containing resins, and polyethyleneimine resins.
[0020] With such a configuration, the gas barrier laminate has better adhesion between the substrate and the gas barrier layer, and can exhibit more stable gas barrier properties.
[0021] (6) The gas barrier laminate according to (5), wherein the surface of the substrate or the surface of the anchor coat layer is a surface that has been subjected to a plasma treatment, the plasma treatment being a glow discharge plasma treatment, and the plasma-treated surface has adhered thereto one or more of silicon, tin, aluminum, indium, magnesium, or any metal belonging to Groups 4 to 12 of the 4th period of the periodic table, or an alloy of silicon, tin, aluminum, indium, magnesium, or any metal belonging to Groups 4 to 12 of the 4th period of the periodic table, or an oxide or nitride of silicon, tin, aluminum, indium, magnesium, or any metal belonging to Groups 4 to 12 of the 4th period of the periodic table.
[0022] With such a configuration, the gas barrier laminate has a more excellent adhesion of the gas barrier layer.
[0023] (7) The substrate is a plastic film, and the gas barrier layer is formed by a vacuum deposition method, has an optical density of 3.4 or more, and has an oxygen permeability of 0.2 cc / m at 22°C and 65% RH. 2 ·day·atm or less, and the water vapor transmission rate at 40℃ and 90% RH is 0.2g / m 2 The gas barrier laminate according to any one of (1) to (6), wherein the gas barrier laminate has a viscosity of 1000 to 2000 s,
[0024] With such a configuration, the gas barrier laminate has excellent light-shielding properties and gas barrier properties, and when applied to a packaging material, the contents can be stored with excellent stability. Effect of the Invention
[0025] According to the present invention, it is possible to provide a gas barrier laminate which has excellent oxygen barrier properties and water vapor barrier properties, and which has excellent oxygen barrier properties even after bending treatment or hot water treatment such as retort treatment. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a photograph showing an example of the appearance of a gas barrier laminate after retort treatment, and shows an example in which the appearance evaluation in Table 1 was "pass." [Diagram 2] FIG. 2 is a photograph showing an example of the appearance of a gas barrier laminate after retort treatment, and shows an example in which the appearance evaluation in Table 1 was "failed, wrinkles all over the surface." [Diagram 3] FIG. 3 is a photograph showing an example of the appearance of a gas barrier laminate after retort treatment, and shows an example in which the appearance evaluation in Table 1 was "failed, partly Al transparent." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] <Gas barrier laminate> The gas barrier laminate according to one embodiment of the present invention is a laminate in which a substrate, a gas barrier layer, and a topcoat layer are laminated in this order. The topcoat layer is made of a mixture of a polyurethane resin and a silane coupling agent. The polyurethane resin contains a polyhydroxyurethane resin having a hydroxyl group. Each of these will be described below.
[0028] (base material) The substrate may be any film used for various packaging materials, and may be a single-layer film or a multi-layer laminate film. The substrate may be appropriately selected depending on the use conditions, such as the type of contents to be packaged and whether or not heat treatment is performed after filling.
[0029] The substrate is not particularly limited, and examples thereof include paper, aluminum foil, cellophane, polyamide resin film, polyester resin film, olefin resin film, acid-modified polyolefin resin film, polystyrene resin film, polyurethane resin film, acetal resin film, uniaxially or biaxially stretched films thereof, K-coat film, and the like. More specifically, the substrate may be a resin film made of low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, polybutene, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, ionomer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid ester copolymer, ethylene-propylene copolymer, methylpentene, polyacrylonitrile, acrylonitrile-styrene copolymer, polycarbonate, polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polyvinylidene fluoride (PVDF), ethylene-tetrafluoroethylene copolymer (ETFE), polytetrafluoroethylene (PTFE), polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, or the like, a K-coated stretched polypropylene film, a K-coated stretched nylon film, or the like.
[0030] Among these, the substrate is preferably a biaxially oriented polyester film such as a polyester film such as polyethylene terephthalate, a uniaxially or biaxially oriented polyamide film such as nylon 6, nylon 66, or MXD6 (polymetaxylylene adipamide), a biaxially oriented polypropylene film (OPP), or a biaxially oriented polyethylene film (BOPE), etc. By selecting these substrates, the gas barrier laminate has superior mechanical properties, heat resistance, etc., compared to non-oriented plastic films, etc.
[0031] The thickness of the substrate is not particularly limited. For example, the thickness of the substrate is preferably 1 μm or more, more preferably 5 μm or more, from the viewpoint of moldability and transparency. The thickness of the substrate is preferably 300 μm or less, more preferably 200 μm or less. When the thickness of the substrate is within the above range, the substrate is likely to withstand various treatments performed when carrying out the lamination step described below, and the flexibility of the resulting gas barrier laminate is excellent, making it easy to obtain a suitable packaging material.
[0032] (Gas barrier layer) The gas barrier layer is provided on the substrate or on the anchor layer described below.
[0033] The gas barrier layer may be a layer made of a gas barrier material that is conventionally used in gas barrier films. The gas barrier layer may be a gas barrier coat made of an organic compound other than an inorganic compound, which will be described later.
[0034] The gas barrier coat is a coating film or the like made of a gas barrier composition that is a hydrolysate of an alkoxide or a hydrolysis condensate of an alkoxide obtained by polycondensing a metal alkoxide and a water-soluble polymer by the sol-gel method in the presence of a sol-gel catalyst, an acid, water, and an organic solvent. However, gas barrier coats that are not water-resistant, such as simple water-soluble polymers such as PVA and EVOH, are not preferable for applications that involve hot water treatment because they have poor resistance to hot water treatment.
[0035] The inorganic compound is not particularly limited. For example, the inorganic compound preferably contains at least one selected from the group consisting of silicon, titanium, tin, zinc, aluminum, indium, and magnesium. The inorganic compound may also be an oxide or nitride of these elements, or an intermetallic compound containing two or more of these elements. This allows the gas barrier layer to be formed as a dense inorganic continuous film, and has excellent gas barrier properties.
[0036] In addition, the gas barrier layer preferably contains at least one of aluminum, silicon oxide, and aluminum oxide. Aluminum, silicon oxide, and aluminum oxide are easy to control during production. Aluminum, silicon oxide, and aluminum oxide can be used as various barrier films, including food packaging materials, and can be applied to various fields.
[0037] Silicon oxide and aluminum oxide are transparent. Therefore, when the gas barrier laminate of the present embodiment is used as a packaging material, it has the advantage that the contents can be visually confirmed, and it can be heated in a microwave oven. When light blocking properties are required, a metal material such as aluminum can be used for the gas barrier layer.
[0038] The thickness of the gas barrier layer is not particularly limited. For example, the thickness of the gas barrier layer is preferably 5 nm or more, more preferably 10 nm or more. The thickness of the gas barrier layer is preferably 100 nm or less. When the gas barrier layer is made of a metal material such as aluminum, the thicker the gas barrier layer, the better the light-shielding property of the gas barrier laminate. The thickness of the gas barrier layer can be appropriately selected depending on the optical density (OD) value. When the thickness of the gas barrier layer is within the above range, the gas barrier laminate has an appropriate manufacturing cost and excellent adhesion between the substrate and the gas barrier layer.
[0039] The method of forming the gas barrier layer is not particularly limited. For example, a gas barrier layer of an inorganic compound can be formed by a conventionally known technique, such as a physical vapor deposition method, a sputtering method, an ion plating method, or a chemical vapor deposition method. The gas barrier layer can also be formed by transfer using a gas barrier layer transfer film.
[0040] (Topcoat layer) The top coat layer is made of a mixture of a polyurethane resin and a silane coupling agent. The top coat layer contains a polyhydroxyurethane resin having a hydroxyl group.
[0041] Here, the polyhydroxyurethane resin has a hydroxyl group (hydroxy group) on the side chain. The polyhydroxyurethane resin has a repeating unit structure represented by the following chemical formula, for example.
[0042] [ka] In the above chemical formula, R1 and R2 each independently represent a hydrocarbon group. The hydrocarbon group is not particularly limited.
[0043] Polyhydroxyurethane can be synthesized by making a five-membered cyclic carbonate compound from an epoxy compound and carbon dioxide, and then subjecting the five-membered cyclic carbonate compound to a polyaddition reaction with a diamine compound. Therefore, polyhydroxyurethane uses carbon dioxide as a raw material instead of an isocyanate compound, which is also environmentally friendly.
[0044] Polyhydroxyurethane is available in the form of a solid resin, a resin solution, a resin water dispersion, etc. The polyhydroxyurethane resin of the present embodiment is preferably an aqueous dispersion from an environmental standpoint. In addition, the aqueous dispersion is preferably one in which at least a part of the carboxyl groups in the polyhydroxyurethane resin structure is neutralized with a basic compound. This allows the aqueous dispersion to have improved film-forming properties. In addition, the gas barrier laminate is likely to exhibit gas barrier properties and the protective function of the gas barrier layer. Furthermore, the gas barrier laminate is likely to be sufficiently dried and cured even at low temperatures and in a short time, and production costs are likely to be reduced.
[0045] Here, many resins having gas barrier properties contain polar groups in order to increase the cohesive force of the polymer. Resins containing polar groups are water-soluble polymers such as polyvinyl alcohol and ethylene-vinyl alcohol copolymers containing hydroxyl groups. However, these resins containing polar groups are water-absorbent and are difficult to impart with hot water treatment resistance. Therefore, the gas barrier laminate of the present embodiment is characterized in that it does not substantially contain a water-soluble polymer and uses a polyhydroxyurethane resin, thereby achieving both hot water treatment resistance and gas barrier properties.
[0046] The hydroxyl groups contained in the polyhydroxyurethane have reactivity and can be used in crosslinking reactions. The polyhydroxyurethane of the present embodiment can also be mixed with other polyurethane resins, which allows the amount of hydroxyl groups contained in the entire polyurethane resin to be controlled.
[0047] In addition, the crosslink density of the polymer is insufficient when the polyhydroxyurethane resin is used alone, and when a laminate intended for use as a packaging material is formed and subjected to a hot-compressed water treatment, the appearance tends to be unsuitable for practical use. Therefore, in this embodiment, a silane coupling agent is added to the top coat layer in order to crosslink the polyhydroxyurethane resin.
[0048] The silane coupling agent is not particularly limited. For example, the silane coupling agent may be a hydrolyzable alkoxysilane compound such as methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, dimethoxydiphenylsilane, hexyltrimethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, trifluoropropyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, N-propyltriethoxysilane, hexyltriethoxysilane, or octyltriethoxysilane; 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; 3-glycidoxypropylmethyldimethoxysilane; 3-glycidoxypropyltrimethoxysilane; Examples of the silane coupling agents include epoxy group-containing silane coupling agents such as methoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, and N-phenyl-3-aminopropyltrimethoxysilane; and methacryl group-containing silane coupling agents such as 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane.
[0049] The top coat of this embodiment can be formed by coating a coating liquid containing a mixture of a polyurethane resin containing polyhydroxyurethane and a silane coupling agent. The content of the silane coupling agent is not particularly limited. As an example, the content of the silane coupling agent is preferably such that the total polyurethane resin containing polyhydroxyurethane and the silane coupling agent are mixed in a mass ratio of 99 / 1 to 80 / 20, more preferably 99 / 1 to 90 / 10, and even more preferably about 95 / 5 to 90 / 10. By the content of the silane coupling agent being within the above range, the gas barrier laminate is less likely to wrinkle and less likely to have poor appearance when a laminate laminate is formed using the gas barrier laminate and subjected to a pressurized hot water treatment.
[0050] The coating liquid may be mixed with a heat stabilizer, an antioxidant, an inorganic layered filler, etc., as long as the coating liquid does not impair its characteristics, appearance, etc. In particular, by mixing an inorganic layered filler, the gas barrier laminate can have improved gas barrier properties.
[0051] The inorganic layered filler is not particularly limited. For example, the inorganic layered filler is montmorillonite, saponite, hectorite, vermiculite, kaolinite, mica, etc. The inorganic layered filler may be naturally occurring or artificially synthesized.
[0052] As described above, the coating liquid of the present embodiment preferably uses water-dispersed polyhydroxyurethane. In addition, when mixing the silane coupling agent with the water-dispersed polyhydroxyurethane resin and other water-dispersed polyurethane resin, the coating liquid may be prepared using a solvent that can be mixed with water, such as alcohols.
[0053] The method for applying the coating liquid is not particularly limited, and examples of the method for applying the coating liquid include a gravure method, a reverse method, a die coater method, a bar coater method, a spray coater method, and a spin coater method.
[0054] The thickness of the topcoat layer is not particularly limited. For example, the thickness of the topcoat layer is preferably 0.1 μm or more, more preferably 0.2 μm or more. The thickness of the topcoat layer is preferably 3 μm or less, more preferably 2 μm or less. By having the thickness of the topcoat layer within the above range, the topcoat layer is likely to exhibit gas barrier properties and protective function of the gas barrier layer, and is likely to be sufficiently dried and cured at low temperatures and in a short time, and the manufacturing cost is likely to be reduced.
[0055] (Anchor coat layer) The gas barrier laminate of the present embodiment preferably has an anchor coat layer between the substrate and the gas barrier layer, which improves adhesion between the substrate and the gas barrier layer and allows the gas barrier laminate to exhibit more stable gas barrier properties.
[0056] The anchor coat layer can be formed by applying an anchor coat agent. The anchor coat agent is not particularly limited. For example, the anchor coat agent is a solvent-based or water-based polyester resin, polyurethane resin, acrylic resin, vinyl alcohol resin, ethylene vinyl alcohol resin, vinyl modified resin, oxazoline group-containing resin, carbodiimide group-containing resin, epoxy group-containing resin, isocyanate group-containing resin, alkoxyl group-containing resin, modified styrene resin, modified silicone resin, etc. Among these, the anchor coat agent is preferably at least one resin selected from the group consisting of polyester resin, polyurethane resin containing polyhydroxyurethane resin having hydroxyl group, acrylic resin, polycarbodiimide resin, oxazoline group-containing resin, and polyethyleneimine resin, from the viewpoint of adhesion and heat resistance. The polyurethane resin as the anchor coat is not particularly limited, and may be various polyurethane resins containing polyhydroxyurethane resin having hydroxyl group used in the top coat layer described above.
[0057] (Surface treatment) Returning to the description of the gas barrier laminate as a whole, the gas barrier laminate of this embodiment may be subjected to various surface treatments on the surface (surface of the substrate or anchor coat layer) before laminating the gas barrier layer. The surface treatment is not particularly limited. As an example, the surface treatment is a vacuum plasma treatment using argon gas or the like, and the vacuum plasma treatment is preferably a glow discharge plasma treatment. In this case, the target material is preferably one or more of silicon, tin, aluminum, indium, or magnesium, or any metal belonging to Groups 4 to 12 of the fourth period of the periodic table, or an alloy of silicon, tin, aluminum, indium, or magnesium, or any metal belonging to Groups 4 to 12 of the fourth period of the periodic table, or one or more of an oxide or nitride of silicon, tin, aluminum, indium, or magnesium, or any metal belonging to Groups 4 to 12 of the fourth period of the periodic table. This makes the gas barrier laminate more excellent in adhesion of the gas barrier layer.
[0058] The vacuum plasma treatment and the glow discharge plasma treatment are performed on the surface before laminating the gas barrier layer. This improves the adhesion between the gas barrier layer and the surface on which the gas barrier layer is formed, and can prevent delamination. Furthermore, by performing the vacuum plasma treatment or the glow discharge plasma treatment, foreign matter attached to the surface can be removed by the generated plasma. In this embodiment, in addition to such surface cleaning, the glow discharge plasma treatment is performed, so that not only the cleaning effect but also a strong adhesion treatment called "nucleation" is performed. As a result, the gas barrier laminate can obtain a stronger adhesion.
[0059] Regarding "core attachment," when a gas barrier material such as aluminum is to be vapor-deposited on the surface of a base layer made of a resin film before laminating a gas barrier, the aluminum atoms are not laminated on the surface of the base film all at once, but are first laminated on the surface of the base film in a dispersed state. Then, using the aluminum atoms as "base points," further aluminum atoms are attached to the periphery of the aluminum atoms at the "base points," which eventually form a layer. However, in this case, if the bond between the aluminum atoms that are the initial base points and the base film is weak, even if the aluminum atoms later gather around the aluminum atoms at the base points to form a layer as if they had grown into a crystal, it is not easy to obtain a layer with excellent interlayer adhesion.
[0060] Therefore, molecules that can easily bond to both the base film and the material laminated on its surface and can increase the bonding strength are scattered on the surface of the base film in advance, and lamination is performed using these as base points, resulting in improved interlayer adhesion. Scattering molecules as base points on the surface of the base film for this purpose is called "nucleation". By performing this nucleation, it is theoretically possible for the gas barrier laminate to improve the interlayer adhesion. Then, by performing vacuum plasma treatment or glow discharge plasma treatment using the above-mentioned target, molecules of the target metal or alloy can be nucleated on the surface of the base film. Furthermore, by mixing oxygen or nitrogen gas with the gas used, molecules of oxide or nitride can be nucleated.
[0061] As described above, the gas barrier laminate of this embodiment has excellent oxygen barrier properties and water vapor barrier properties, and also has excellent oxygen barrier properties after bending treatment or hot water treatment such as retort treatment.
[0062] Specifically, in the gas barrier laminate of the present embodiment, when the substrate is a plastic film and the gas barrier layer is formed by a vacuum deposition method, the optical density is 3.4 or more, and the oxygen permeability at 22°C and 65% RH is 0.2 cc / m 2·day·atm or less, and the water vapor transmission rate at 40℃ and 90% RH is 0.2g / m 2 ·days or less. Such a gas barrier laminate is suitable as a food packaging material, etc. And, the packaging material to be treated with compressed hot water is preferably used in a laminate configuration in which unstretched polypropylene is laminated as a sealant layer on the back side of the topcoat layer of the gas barrier laminate, and further, a polyamide film is laminated on the outermost layer on the topcoat layer side of the gas barrier laminate in order to impart pinhole resistance strength and toughness, and further, a polyethylene terephthalate film is laminated to prevent the strength reduction and shrinkage of the polyamide film due to hot water.
[0063] The optical density is preferably 3.4 or more, and more preferably 3.6 or more. When the optical density is in the above range, the gas barrier laminate has excellent light-shielding properties when used as a packaging material and light-shielding properties are required.
[0064] Oxygen permeability at 22℃ and 65%RH is 0.2cc / m 2 ·day·atm or less is preferable, and 0.1cc / m 2 By having the oxygen transmission rate at a temperature of 22° C. and a humidity of 65% RH within the above range, the gas barrier laminate has oxygen barrier properties that make it suitable for use as an alternative to aluminum foil.
[0065] Water vapor transmission rate at 40℃ and 90% RH is 0.2g / m 2 ·day or less, and 0.1 g / m 2 By having the water vapor transmission rate at 40° C. and 90% RH within the above range, the gas barrier laminate has water vapor barrier properties that enable it to be used as a substitute for aluminum foil.
[0066] In this embodiment, the pressurized hot water resistance of the gas barrier laminate, in the case of the laminate structure described above, is evaluated by checking the oxygen transmission rate, adhesion, and appearance including optical density after immersing a test piece in hot water at 125°C for 30 minutes, and determining whether the performance is maintained even after the pressurized hot water treatment. As a result, the gas barrier laminate has an oxygen transmission rate of 0.4 cc / m2 or more by the isobaric method (Method A described in JIS K 7126-2) even after heat treatment in hot water at 125°C for 30 minutes. 2 The gas barrier layer does not become transparent even in the case of an aluminum vapor deposition layer, and the optical density is maintained at 3.0 or more, thereby exhibiting excellent light-blocking properties and a good appearance.
[0067] The gas barrier laminate of this embodiment also has excellent flex resistance. The flex resistance is evaluated by evaluating the oxygen permeability after bending a laminate having a surface of a topcoat layer and a linear low-density polyethylene bonded thereto as a sealant layer three times using a Gelbo flex tester in accordance with ASTM-E-392-74, and by determining whether the performance is maintained even after the bending test. As a result, the gas barrier laminate had an oxygen permeability of 0.2 cc / m2 even after being subjected to a load of bending three times using the Gelbo flex tester. 2 ·day·atm or less, and good oxygen barrier properties can be maintained.
[0068] Furthermore, the gas barrier laminate of this embodiment can also show excellent results when the gas barrier layer is a silicon oxide vapor deposition layer formed by a vacuum deposition method. That is, the gas barrier laminate has a substrate of a PET film, a gas barrier layer of a silicon oxide vapor deposition layer formed by a vacuum deposition method, and when a top coat layer is provided, the oxygen permeability at a temperature of 22°C and a humidity of 65% RH is 0.1 cc / m 2 Water vapor transmission rate of 0.5g / m at 40℃ and 90%RH. 2·day or less. Such a gas barrier laminate is suitable for use as a food packaging material, etc. The packaging material to be treated with compressed hot water is preferably used in the form of a laminate in which a polyamide film is laminated to the surface of the top coat layer of the gas barrier laminate in order to impart pinhole resistance and toughness, and unstretched polypropylene is further laminated as a sealant layer.
[0069] In this embodiment, the hot-compressed water resistance of the gas barrier laminate, when configured as the above laminate, is evaluated by checking the oxygen transmission rate and adhesion after immersing a test piece in hot water at 125°C for 30 minutes, and whether the performance is maintained even after the hot-compressed water treatment. As a result, the gas barrier laminate has an oxygen transmission rate of 0.5 cc / m2 or more by the isobaric method (method A of JIS K 7126-2) even after heat treatment in hot water at 125°C for 30 minutes. 2 The gas barrier layer did not peel off from the topcoat layer.
[0070] Furthermore, oxide vapor-deposited films such as silicon oxide vapor-deposited films tend to have inferior flex resistance compared to metal vapor-deposited films such as aluminum vapor-deposited films, but the gas barrier laminate of this embodiment also has excellent flex resistance. In this embodiment, the flex resistance of the gas barrier laminate is evaluated by evaluating the oxygen permeability after bending three times in accordance with ASTM-E-392-74 using a Gelbo flex tester in a laminate configuration in which linear low-density polyethylene is bonded to the surface of a topcoat layer as a sealant layer, and whether or not the performance is maintained even after the bending test. As a result, the gas barrier laminate had an oxygen permeability of 0.3 cc / m even after being subjected to a load of bending three times using the Gelbo flex tester. 2 ·day·atm or less, and good oxygen barrier properties can be maintained. EXAMPLES
[0071] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0072] Example 1 A biaxially stretched polyethylene terephthalate film was subjected to a GD treatment (glow discharge plasma treatment) using SUS304 as a surface treatment, and aluminum was formed to a thickness of 70 nm by vacuum deposition as a gas barrier layer to produce an aluminum deposition film. W-011A and W-013A (both manufactured by Dainichiseika Chemicals Co., Ltd.) were prepared as aqueous dispersions of polyhydroxyurethane resin. Both contained 1% or less of 25% ammonia water, and all or some of the carboxyl groups were neutralized, resulting in a weakly basic aqueous dispersion. The oxygen transmission rate (23°C, 65% RH) of each resin alone was as follows. W-011A 10cc 20μm / m 2 ·day·atm W-013A 1cc 20μm / m 2 ·day·atm
[0073] (Mixture 1A) Preparation 1A was prepared by mixing and stirring 15.83 parts of an aqueous dispersion of polyhydroxyurethane resin (W-013A manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., coating liquid resin concentration 30% by weight) and 25.16 parts of water. (Mixture 1B) Preparation 1B was prepared by mixing and stirring 0.13 parts of an epoxy silane coupling agent (Dynasylan GLYMO, manufactured by Evonik Japan Co., Ltd.), 0.13 parts of a metal alkoxide (Dynasylan A, manufactured by Evonik Japan Co., Ltd.), 0.05 parts of 3.5% hydrochloric acid, and 58.71 parts of isopropyl alcohol. (Coating Liquid 1) While stirring Preparation 1A, Preparation 1B was added to Preparation 1A, mixed, and further stirred to prepare Coating Solution 1. Coating Solution 1 was applied to the surface of the gas barrier layer of an aluminum vapor-deposited film by a bar coater method, and dried to form a top coat layer, thereby producing Gas Barrier Laminate 1. The thickness of the obtained top coat layer was 0.5 μm.
[0074] Example 2 (Mixture 2A) Mixture 2A was prepared by mixing and stirring 2.50 parts of an aqueous dispersion of polyhydroxyurethane resin (W-013A, manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., coating liquid resin concentration 30% by weight), 17.39 parts of an aqueous dispersion of polyurethane resin (Exp. SC-519A, manufactured by DIC Corporation), and 23.94 parts of water. (Mixture 2B) Preparation 2B was prepared by mixing and stirring 0.13 parts of an epoxy silane coupling agent (Dynasylan GLYMO, manufactured by Evonik Japan Co., Ltd.), 0.13 parts of a metal alkoxide (Dynasylan A, manufactured by Evonik Japan Co., Ltd.), 0.05 parts of 3.5% hydrochloric acid, and 55.87 parts of isopropyl alcohol. (Coating Fluid 2) While stirring Preparation 2A, Preparation 2B was added to Preparation 2A, mixed, and further stirred to prepare Coating Liquid 2. Except for coating Coating Liquid 2 on the surface of the gas barrier layer of an aluminum vapor-deposited film by a bar coater method and drying to form a topcoat layer, a gas barrier laminate 2 was produced in the same manner as in Example 1. The thickness of the obtained topcoat layer was 0.5 μm.
[0075] Example 3 (Mixture 3A) Preparation 3A was prepared by mixing and stirring 1.67 parts of an aqueous dispersion of polyhydroxyurethane resin (W-013A, manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., coating liquid resin concentration 30% by weight), 18.48 parts of an aqueous dispersion of polyurethane resin (Exp. SC-519A, manufactured by DIC Corporation), and 39.78 parts of water. (Mixture 3B) Preparation 3B was prepared by mixing and stirring 0.13 parts of an epoxy silane coupling agent (Dynasylan GLYMO, manufactured by Evonik Japan Co., Ltd.), 0.13 parts of a metal alkoxide (Dynasylan A, manufactured by Evonik Japan Co., Ltd.), 0.05 parts of 3.5% hydrochloric acid, and 39.78 parts of isopropyl alcohol. (Coating Fluid 3) While stirring Preparation 3A, Preparation 3B was added to Preparation 3A, mixed, and further stirred to prepare Coating Solution 3. Except for the fact that Coating Solution 3 was applied to the surface of the gas barrier layer of an aluminum vapor-deposited film by a bar coater method and dried to form a topcoat layer, Gas Barrier Laminate 3 was produced in the same manner as in Example 1. The thickness of the obtained topcoat layer was 0.5 μm.
[0076] Example 4 (Mixture 4A) Preparation solution 4A was prepared by mixing and stirring 1.67 parts of an aqueous dispersion of polyhydroxyurethane resin (W-013A, manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., coating liquid resin concentration 30% by weight), 18.48 parts of an aqueous dispersion of polyurethane resin (Exp. SC-519A, manufactured by DIC Corporation), and 39.78 parts of water. (Compound Solution 4B) Preparation 4B was prepared by mixing and stirring 0.13 parts of an epoxy silane coupling agent (Dynasylan GLYMO, manufactured by Evonik Japan Co., Ltd.), 0.13 parts of a metal alkoxide (Dynasylan A, manufactured by Evonik Japan Co., Ltd.), 0.05 parts of 3.5% hydrochloric acid, and 39.78 parts of isopropyl alcohol. (Coating Fluid 4) While stirring Preparation 4A, Preparation 4B was added to Preparation 4A, mixed, and further stirred to prepare Coating Solution 4. Except for coating Coating Solution 4 on the surface of the gas barrier layer of an aluminum vapor-deposited film by a bar coater method and drying to form a topcoat layer, a gas barrier laminate 4 was produced in the same manner as in Example 1. The thickness of the obtained topcoat layer was 0.5 μm.
[0077] Example 5 A silicon oxide film was prepared by forming a gas barrier layer of 10 nm on the coated surface of a biaxially oriented polyethylene terephthalate film on which an anchor coat layer had been formed in advance. Coating solution 1 was applied to the surface of the gas barrier layer of the silicon oxide film by a bar coater method, and dried to form a top coat layer. Gas barrier laminate 5 was prepared in the same manner as in Example 1. The thickness of the obtained top coat layer was 0.5 μm.
[0078] Comparative Example 1 (Mixture 5A) Preparation 5A was prepared by mixing and stirring 52.17 parts of an aqueous dispersion of polyurethane resin (Exp. SC-519A, manufactured by DIC Corporation) and 23.91 parts of water. (Coating Fluid 5) While stirring Preparation Liquid 5A, 23.91 parts of isopropyl alcohol was added to Preparation Liquid 5A, mixed, and further stirred to prepare Coating Liquid 5. Except for coating Coating Liquid 5 on the surface of the gas barrier layer of an aluminum vapor-deposited film by a bar coater method and drying to form a topcoat layer, a gas barrier laminate 6 was produced in the same manner as in Example 1. The thickness of the obtained topcoat layer was 0.5 μm.
[0079] Comparative Example 2 (Preparation 6A) Preparation 6A was prepared by mixing and stirring 20.65 parts of an aqueous dispersion of polyurethane resin (Exp. SC-519A, manufactured by DIC Corporation) and 39.52 parts of water. (Preparation 6B) Preparation 6B was prepared by mixing and stirring 0.13 parts of an epoxy silane coupling agent (Dynasylan GLYMO, manufactured by Evonik Japan Co., Ltd.), 0.13 parts of a metal alkoxide (Dynasylan A, manufactured by Evonik Japan Co., Ltd.), 0.05 parts of 3.5% hydrochloric acid, and 39.52 parts of isopropyl alcohol. (Coating Fluid 6) While stirring Preparation 6A, Preparation 6B was added to Preparation 6A, mixed, and further stirred to prepare Coating Solution 6. Except for coating Coating Solution 6 on the surface of the gas barrier layer of an aluminum vapor-deposited film by a bar coater method and drying to form a topcoat layer, a gas barrier laminate 7 was produced in the same manner as in Example 1. The thickness of the obtained topcoat layer was 0.5 μm.
[0080] Comparative Example 3 (Preparation 7A) Preparation 7A was prepared by mixing and stirring 1.67 parts of an aqueous dispersion of polyurethane resin (WPB341 manufactured by Mitsui Chemicals, Inc.), 18.48 parts of an aqueous dispersion of polyurethane resin (Exp. SC-519A manufactured by DIC Corporation), and 39.78 parts of water. (Compound Solution 7B) Preparation 7B was prepared by mixing and stirring 0.13 parts of an epoxy silane coupling agent (Dynasylan GLYMO, manufactured by Evonik Japan Co., Ltd.), 0.13 parts of a metal alkoxide (Dynasylan A, manufactured by Evonik Japan Co., Ltd.), 0.05 parts of 3.5% hydrochloric acid, and 39.78 parts of isopropyl alcohol. (Coating Fluid 7) While stirring Preparation 7A, Preparation 7B was added to Preparation 7A, mixed, and further stirred to prepare Coating Solution 7. Except for coating Coating Solution 7 on the surface of the gas barrier layer of an aluminum vapor-deposited film by a bar coater method and drying to form a topcoat layer, a gas barrier laminate 8 was produced in the same manner as in Example 1. The thickness of the obtained topcoat layer was 0.5 μm.
[0081] Comparative Example 4 The aluminum vapor-deposited film was evaluated without forming a topcoat layer. A laminate was produced in the same manner as in Example 1, except that no topcoat layer was formed.
[0082] Comparative Example 5 The silicon oxide vapor-deposited film was evaluated without forming a topcoat layer. A laminate was produced in the same manner as in Example 5, except that no topcoat layer was formed.
[0083] The composition of the coating liquid is shown in Table 1. The laminates of the above-mentioned Examples and Comparative Examples were evaluated for optical density, oxygen permeability, water vapor permeability, retort resistance, flex resistance, and adhesion by the following evaluation methods. The results are shown in Table 1.
[0084] [Table 1]
[0085] <Optical density OD> The optical density (OD) of the gas barrier laminate and the laminate was measured using a transmission densitometer (T5 plus) manufactured by Ihara Electronics Co., Ltd. An optical density of 3.4 or more was considered to be acceptable. In addition, after retort treatment, a density of 3.0 or more and an OD reduction of 0.4 or less were considered to be acceptable.
[0086] <Evaluation of oxygen permeability> The oxygen permeability was measured under conditions of temperature 22°C and humidity 65% RH using an oxygen permeability measuring device (OX-TRAN 2 / 21) manufactured by MOCON, based on the method A described in JIS K 7126-2. The oxygen permeability value was 0.2 cc / m for the gas barrier laminate when the gas barrier layer was an aluminum vapor deposition layer. 2 ·day·atm or less, after retort processing it is 0.4cc / m 2 ·day·atm or less, 0.2cc / m after bending test 2 ·day·atm or less, and the increase in oxygen permeability through the gas barrier laminate is 0.2cc / m 2 In Table 1, "after bending test" indicates that the bending resistance test was performed using the Gelbo flex tester described later.
[0087] <Evaluation of water vapor transmission rate> The water vapor transmission rate was measured under conditions of a temperature of 40°C and a humidity of 90 RH% using a water vapor transmission rate measuring device (PERMATRAN-W 3 / 33) manufactured by MOCON, based on the method B described in JIS K 7129. When the gas barrier layer was an aluminum vapor deposition layer, the water vapor transmission rate was 0.2 g / m 2 If the gas barrier layer is a silicon oxide vapor deposition layer, the gas barrier laminate must have a thickness of 0.5 g / m 2 The pass mark was rated as less than 100 days.
[0088] <Retort resistance> On the side opposite the topcoat layer, apply 4.0 g / m (solids) 2 A CPP (P1146, non-oriented polypropylene, thickness: 60 μm, manufactured by Toyobo Co., Ltd.) was provided as a sealant film via a dry lamination adhesive of 1.0 g / m2. 2 A laminate was produced by applying ONy (ONBC, oriented nylon, thickness: 15 μm, manufactured by Unitika Co., Ltd.) and then PET (E5100, polyethylene terephthalate, thickness: 12 μm, manufactured by Toyobo Co., Ltd.) to the surface of the topcoat layer side of the gas barrier laminate via the dry lamination adhesive of each of the above. The laminate was immersed in hot water at 125° C. for 30 minutes and subjected to retort treatment, after which the oxygen permeability was 0.4 cc / m 2 ·day·atm or less was deemed to pass.
[0089] <Bending resistance> On the surface of the topcoat layer, apply 4.0 g / m (solid content) 2 A laminate was prepared by providing an LLDPE (TUX FC-S, linear low density polyethylene, thickness: 50 μm, manufactured by Mitsui Chemicals Tohcello Co., Ltd.) as a sealant film via the dry lamination adhesive. The laminate was bent three times using a Gelbo flex tester in accordance with ASTM-E-392-74, and then the oxygen permeability was evaluated. The bending resistance was evaluated when the oxygen permeability after the bending test using the Gelbo flex tester was 0.2 cc / m 2·day·atm or less, and the increase in oxygen permeability through the gas barrier laminate is 0.2cc / m 2 ·day·atm or less was deemed to pass.
[0090] <Adhesion> In the case where the gas barrier layer of the gas barrier laminate is an aluminum vapor deposition layer formed by a vacuum deposition method, a coating amount (solid content) of 4.0 g / m is applied to the surface of the gas barrier laminate opposite to the top coat layer. 2 A CPP (P1146, non-oriented polypropylene, thickness: 60 μm, manufactured by Toyobo Co., Ltd.) was provided as a sealant film via a dry lamination adhesive of 1.0 g / m2. 2 A laminate was prepared by providing ONy (ONBC, stretched nylon, thickness: 15 μm, manufactured by Unitika Co., Ltd.) and then PET (E5100, polyethylene terephthalate, thickness: 12 μm, manufactured by Toyobo Co., Ltd.) on the topcoat layer side of the gas barrier laminate via the dry lamination adhesives mentioned above. The laminate was cut into strips with a width of 15 mm before and after retort treatment, and the laminate strength between ONy and the gas barrier laminate was evaluated by peeling at a peel speed of 300 mm / min and 180° peeling. During peeling, it was also confirmed whether peeling occurred between the gas barrier layer and the topcoat layer. The adhesion was evaluated as passing when there was no peeling between the gas barrier layer and the topcoat layer and the laminate strength was 1.2 N / 15 mm or more. On the other hand, when the gas barrier layer of the gas barrier laminate is a silicon oxide vapor deposition layer formed by a vacuum deposition method, ONy (ONBC, oriented nylon, thickness: 15 μm, manufactured by Unitika Ltd.) was provided on the surface of the top coat layer side of the gas barrier laminate via a dry lamination adhesive with a coating amount (solid content) of 4.0 g / m. 2A CPP (P1146, non-oriented polypropylene, thickness: 60 μm, manufactured by Toyobo Co., Ltd.) was provided as a sealant film via the dry lamination adhesive described above to prepare a laminate. The laminate was cut into strips with a width of 15 mm before and after retort treatment, and the lamination strength between the ONy and the gas barrier laminate was evaluated by peeling at a peel speed of 300 mm / min and 180° peeling. It was also confirmed whether peeling occurred between the gas barrier layer and the topcoat layer during peeling.
[0091] [Table 2]
[0092] As shown in Table 2, the gas barrier laminates of Examples 1 to 5 of the present invention had excellent oxygen barrier properties and water vapor barrier properties, and the oxygen barrier properties were also excellent after bending treatment and hot water treatment such as retort treatment.
[0093] In Table 2, the optical density of Example 5 is marked "-" because the gas barrier layer is silicon oxide SiOx and light blocking properties are not required, so evaluation was omitted. In Comparative Examples 1, 3, and 4, the gas barrier laminates were not evaluated for flex resistance because the oxygen transmission rate or the sample appearance after retort treatment did not pass the required standard.
[0094] FIG. 1 is a photograph showing an example of the appearance of a gas barrier laminate after retort treatment, showing an example with an appearance evaluation of "pass" in Table 1. FIG. 2 is a photograph showing an example of the appearance of a gas barrier laminate after retort treatment, showing an example with an appearance evaluation of "fail, wrinkles all over" in Table 1. FIG. 3 is a photograph showing an example of the appearance of a gas barrier laminate after retort treatment, showing an example with an appearance evaluation of "fail, partial aluminum transparency" in Table 1.
Claims
1. A substrate, a gas barrier layer, and a top coat layer are laminated in this order, The top coat layer is made of a mixture of a polyurethane resin and a silane coupling agent, The gas barrier laminate, wherein the polyurethane resin comprises a polyhydroxyurethane resin having a hydroxyl group.
2. The top coat is formed by applying an aqueous dispersion of a polyhydroxyurethane resin, 2. The gas barrier laminate according to claim 1, wherein in the aqueous dispersion, at least a portion of the carboxy groups in the polyhydroxyurethane resin structure is neutralized with a basic compound.
3. 3. The gas barrier laminate according to claim 1, wherein the gas barrier layer contains at least one of silicon, titanium, tin, zinc, aluminum, indium, magnesium, and oxides or nitrides thereof.
4. 3. The gas barrier laminate according to claim 1, wherein the gas barrier layer contains at least one of aluminum, silicon oxide, and aluminum oxide.
5. An anchor coat layer is provided between the substrate and the gas barrier layer, 3. The gas barrier laminate according to claim 1, wherein the anchor coat layer is formed from at least one resin selected from the group consisting of a polyester resin, a polyurethane resin including a polyhydroxyurethane resin having a hydroxyl group, an acrylic resin, a polycarbodiimide resin, an oxazoline group-containing resin, and a polyethyleneimine resin.
6. The surface of the substrate or the surface of the anchor coat layer is a surface that has been subjected to a plasma treatment, The plasma treatment is a glow discharge plasma treatment, 6. The gas barrier laminate according to claim 5, wherein the surface subjected to the plasma treatment is adhered with one or more of silicon, tin, aluminum, indium, magnesium, or any metal belonging to Groups 4 to 12 of the 4th period of the periodic table, or an alloy of silicon, tin, aluminum, indium, magnesium, or any metal belonging to Groups 4 to 12 of the 4th period of the periodic table, or an oxide or nitride of silicon, tin, aluminum, indium, magnesium, or any metal belonging to Groups 4 to 12 of the 4th period of the periodic table.
7. The substrate is a plastic film, The gas barrier layer is formed by a vacuum deposition method, The optical density is 3.4 or more, Oxygen permeability at 22°C and 65% RH is 0.2 cc / m 2 ・Day・atm or less, Water vapor transmission rate at 40°C and 90% RH is 0.2 g / m 2 3. The gas barrier laminate according to claim 1 or 2, wherein the gas barrier laminate has a thermal conductivity of 0.05 to 0.5 s.day or less.
Citation Information
Patent Citations
Laminated film
JP2019188658A